Relationship Between the Xylem Anatomy of Grapevine Rootstocks and Their Susceptibility to Phaeoacremonium minimum and Phaeomoniella chlamydospora - Ramsing, Charis K.; Gramaje, David; Mocholí, Sara; Agustí, Javier; Cabello Sáenz de Santa María, Félix; Armengol, Josep; Berbegal, Mónica (Frontiers in Plant Science, 2021)
Fungal grapevine trunk diseases (GTDs) are some of the most pressing threats to grape production worldwide. While these diseases are associated with a number of fungal pathogens, Phaeomoniella chlamydospora and Phaeoacremonium minimum are important contributors to esca and Petri. Recent research has linked grapevine xylem diameter with tolerance to Pa. chlamydospora in commercial rootstocks. Here we screen over 25 rootstocks for xylem characteristics and tolerance to both Pa. chlamydospora and Pm. minimum. Tolerance was measured by fungal incidence and DNA concentration (quantified via qPCR), while histological analyses were used to measure xylem characteristics, including xylem vessels diameter, density and the proportion of the stem surface area covered by xylem vessels. Rootstocks were grouped into different classes based on xylem characteristic to assess the potential association between vasculature traits and disease tolerance. Our results revealed significant differences in all the analyzed xylem traits, and also in DNA concentration for both pathogens among the tested rootstocks. They corroborate the link between xylem vessels diameter and tolerance to Pa. chlamydospora. In Pm. minimum, the rootstocks with the widest xylem diameter proved the most susceptible. This relationship between vasculature development and disease tolerance has the potential to inform both cultivar choice and future rootstock breeding to reduce the detrimental impact of GTDs worldwide.